Fetal developmental programing: insights from human studies and experimental models - Lopes, Gisele Aparecida Dionísio [UNESP]; Ribeiro, Vinícius Luís Bertotti [UNESP]; Barbisan, Luís Fernando [UNESP]; Marchesan Rodrigues, Maria Aparecida [UNESP] (Taylor & Francis, 2017)
Background: Environmental factors, particularly nutrition during pregnancy and early life can influence the risk of chronic diseases in later life. The underlying mechanism, termed “programing”, postulates that an environmental stimulus during a critical window of time, early in life, has a permanent effect on subsequent structure and function of the organism. Objective: In this study we review the concept of fetal programing on chronic diseases and the proposed hypotheses for the association between early development and later disease, including epigenetic variation. We concentrate on specific aspects of maternal nutrition, particularly under-nutrition and over-nutrition, in humans and animal models. Conclusion: An adequate maternal nutrition during pregnancy is crucial for the health outcome of the offspring at adulthood.
Keywords: Developing countries; epigenetic process; fetal developmental programing; maternal over-nutrition; maternal under-nutrition